PENGALAMAN KOMUNIKASI DOSEN DALAM MENJALANI PEMBELAJARAN DARING DI UPN VETERAN JAKARTA - Destiani Ayu Saputri (2022)
The stipulation of the pandemic situation in March 2020 create various policies that ultimately changed the way we operate, including the world of education. One of them is the distance learning policy which is also implemented at UPN Veterans Jakarta. This phenomenon is a new experience for the majority of lecturers and students who change the way they communicate. Seeing this, the researcher wants to find out how the process or the actual experience by lecturers while undergoing communication in online learning in a pandemic situation, especially lecturers at UPN Veterans Jakarta using interpersonal communication theory. The method used in this research is qualitative with a phenomenological approach. Through in-depth interview data collection with 10 informants, it was found a few themes, including 1) Difficulty at the beginning, 2) Differentquality and attitude of students, 3) Interaction was reduced, 4) It was difficult to control students. , 5) Network barriers, 6) More mentally tired, 7) Time efficiency and flexibility, 8) Longer preparation, 9) Using whatsapp media, 10) Asking for feedback from students, 11) Making innovations, 12) Establishing good relationships, but still distant, 13) Communication is constructive and open, 14) More understanding, 15) Collaboration online. Furthermore, the meaning obtained is that there was a surprise by the lecturers at the beginning but in the end they were able to adapt and even choose to apply the collaborative method in the future. However, online learning is still considered to have limitations that cannot replace face-to-face communication activities, so it is only complementary.